(untitled) (Journal of Libya for geographical studies, 2026)
Several regions in Morocco are exposed to flood hazards as a result of the interaction between various natural and human factors. These floods are neither recent nor solely the product of current conditions; rather, their occurrence dates back several decades. However, climate change, along with the widespread expansion of vulnerability patterns, has significantly increased the likelihood of flood events across many Moroccan territories. The scientific value of this study lies in addressing a critical issue that has become increasingly pressing for all stakeholders involved in territorial management at the central, regional, and local levels—namely, flood risk, which causes substantial human and material losses when it occurs. The main objective of this research is to highlight the evolution of flood hazards in Morocco by compiling a comprehensive inventory of major flood events that have affected the national territory since the mid-twentieth century. The study also aims to establish an inclusive classification of the most threatened areas, determine their levels of risk, and examine the key factors responsible for flood formation, as well as the measures adopted for flood prevention and management. The findings indicate that most regions within Moroccan territory—whether in the north, east, southeast, or west—are exposed to flood hazards, underscoring the urgent need for intensified efforts toward rational and sustainable management of this natural risk.